Pengaruh Beberapa Jenis Bioaktivator Terhadap Pengomposan dan Kandungan Hara N, Fe pada Kompos Limbah Kempaan Daun Gambir (Uncaria Gambir Roxb) - Meylin K Saragih; Friska Juliana Simbolon; N M Ginting (Musamus Journal of Agrotechnology Research, 2020)
This study aims to determine the effect of several types of bioactivators on composting and nutrient content of N and Fe in the compost of Kempaan leaf gambier waste. This research was conducted at the Compost House of the Faculty of Agriculture, Methodist University of Indonesia, Tanjung Sari, Medan Selayang District, Medan City, with a height of ± 32 meters above sea level (asl), which was carried out from January 2019 to February 2019. This study used a total of 3 treatment. The first treatment of EM-4 consisted of 1 level of P1 = 10 ml EM- 4/1 liter of water / 10 kg of gambier leaf compressed waste, the second treatment of Bio-Triba consisted of 3 levels of P2 = 8 ml of Bio-Triba / 1 liter of water. / 10 kg of gambier leaf compressed waste, P3 = 10 ml Bio-Triba / 1 liter water / 10 kg gambier leaf compressing waste, P4 = 12 ml Bio-Triba / 1 liter water / 10 kg gambier leaf compressing waste, third treatment giving M -Dec with 4 levels P5 = 8g M-Dec / 1 liter water / 10 kg gambier leaf compressed waste, P6 = 10g M-Dec / 1 liter water / 10 kg gambier leaf compressed waste, P7 = 12g M-Dec / 1 liter water / 10 kg of gambier leaf compressed waste, P8 = 14g M-Dec / 1 liter of water / 10 kg gambier leaf compressed waste. The results of this study indicate that the effect of several types of bioactivators on the composting of Gambir leaf pressed waste against EM-4, Bio-Triba, and M-Dec treatment on the nutrient content of N-Total, Fe and C / N ratio has met the Specifications for Organic Compost SNI 19- 7030-2004. However, the content of C-Organic, moisture content and pH do not meet the SNI 19-7030-2004 Organic Compost Specifications. Keywords: Gambir Leaves Campaign Waste, Bioactivator, N, Fe